Superman [compact disc, unabridged] : the high-flying history of America's most enduring hero - Tye, Larry (Books on Tape ; Random House Audio, 2012)
Larry Tye chronicles the adventures of the men and women who kept Siegel and Shuster's "Man of tomorrow" aloft and vitally alive through seven decades and counting. Here are the savvy publishers and visionary writers and artists of comics' Golden Age who ushered the red-and-blue-clad titan through changing eras and evolving incarnations; and the actors, including George Reeves and Christopher Reeve, who brought the Man of Steel to life on screen.